Wages or Legitimacy? A Qualitative Analysis of Home Care Worker Perspectives in Choosing Work Settings - Christine Kelly PhD; Lisette Dansereau PhD; Jennifer C. H. Sebring MSc; Yeonjung Lee PhD; Allison Williams PhD (SAGE Publishing, 2024)
Directly-Funded (DF) home care allows users to organize and purchase their own care services and is expanding globally. Little is known about the career pathways of home care workers. Our study asks, what experiences and factors do home care workers consider when choosing a work setting? And, specifically, what influences their decisions to work directly for their clients? Framed with Cranford's (2020) flexibility-security matrix for analyzing home care dynamics, we remotely interviewed 20 home care workers in two Canadian provinces. Three team members conducted axial coding and thematic analysis using Dedoose software. We identified personal and material factors at the intimate and labor market level that workers weigh when choosing whether to work for an agency or directly for a client. At the intimate level, workers value the flexibility, autonomy, and respect facilitated in care relations when working directly for a client. At the labor market level, agencies provide better job security and the benefit of supervisory support but lower wages. Additionally, as care work often serves as a stepping stone for immigration and citizenship agency positions are considered a more "legitimate" option than working directly for a client. Our study shows that workers directly employed by their clients enjoy more flexibility but lack security, whereas agency employed workers risk immediate reductions in working conditions in exchange for limited improvements in safety and supervision and, like other frontline care work, DF home care represents a key career pathway for immigrants with previous experience in health and social care settings.